BURNOUT SYNDROME OF NURSES IN INPATIENT UNITS - Nursinta Dame Manullang; Yenni Ferawati Sitanggang; Masrida Adolina Panjaitan (Nursing Current: Jurnal Keperawatan, 2021)
Burnout is a state of physical, emotional and mental stress caused by chronic workplace pressure. Nurses are often confronted with stress-laden situations related to varied functions and extent of responsibilities causing the burnout syndrome. This study aims to describe the burnout level of inpatient nurses working in the (inpatient) units of a private hospital in West Java. This is a descriptive quantitative study conducted among all the 54 nurses in this hospital’s inpatient units. The Maslach Burnout Inventory-Human Services Survey (MBIHSS), a tool that measures three dimensions of the burnout syndrome: personal accomplishments, emotional exhaustion and depersonalization, was used. Data collected were analysed with the univariate analysis that described the respondents’ characteristics and their responses on the MBI-HSS. Results showed that majority of the respondents are females (94.4%); more than half (61.1%) have a Bachelor of Nursing degree; 74.1% are in the 20-30 years age group; and 51.9% had more than one year of work experience. Moreover, the respondents rated depersonalization characterized by feelings of unreality and strangeness about one's own behaviour as the dimension that highly contributed to burnout (98%). Emotional exhaustion, the feelings of being emotionally overextended and exhausted by one's work was rated low (40.7%). Moreover, personal achievement that measures feelings of competence and successful achievement in one's work had a high 70.4%. The researchers recommend that administrators provide nursing staff with continuing education sessions on strategies to effectively cope with stressful situations in the workplace to counter the burnout syndrome.